Assessing the Effects of Capital Structure and Corporate Governance on Financial Performance: Evidence from PT Bank Ganesha Tbk - Euis Nessia Fitri (SEAN Institute, 2024)
This study aims to analyze the influence of capital structure and corporate governance on the financial performance of PT Bank Ganesha Tbk. The research employs a quantitative approach using multiple linear regression analysis. The population in this study consists of all monthly financial data of PT Bank Ganesha Tbk from 2017 to 2023. The sample was obtained through a census technique by interpolating annual data into monthly data, resulting in 84 observations. The variables examined include the Debt to Equity Ratio (DER) as a proxy for capital structure, board size and the number of independent commissioners as indicators of corporate governance, and Net Interest Margin (NIM) as a measure of financial performance. The results show that capital structure and independent commissioners have a significant positive effect on financial performance, while board size does not show a significant influence. These findings underscore the importance of aligning financial strategies with effective governance practices in the banking sector.